Nieuchronny plagiat Prawo autorskie w nowoczesnym dyskursie literackim - Jakubowiak, Maciej (Nowa Humanistyka, 2017)
The book addresses the problem of the influence of copyright law on modern modes of functioning and understanding of literature. This problem is situated in a context of Law and Literature studies and in particular within the cultural studies of copyright, which are summarised in chapter one. The history of copyright law and related literary discussions is recapitulated in chapter two. In the next chapters, the analysis is focused on literary discussions in which copyright law is a directly posed problem, or it is indicated only as context. Particular attention is paid to: philological genealogical research (and texts by Wacław Borowy and John Livingstone Lowes); discussion surrounding T.S. Eliot's poem 'The Waste Land'; the debate provoked by Karol Irzykowski's article 'Plagiatowy charakter przełomów literackich w Polsce' ['The Plagiarising Character of Literary Breakthroughs in Poland']; analysis of copyright law in the writings of Jacques Derrida and in the novel Muza dalekich podróży [The Muse of Long-Distance Travels] by Teodor Parnicki; finally, anthologies Future of Copyright published at the beginning of the twenty-first century in Poland. In the last chapter, the analysed problems are situated in the context of the debate on the commodification of literature in capitalist societies.